2021
DOI: 10.1007/s00068-021-01777-y
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of burn patients admitted in the Netherlands: a nationwide registry study investigating incidence rates and hospital admission from 2014 to 2018

Abstract: Purpose The aim of this study was to gain insight into the epidemiology of burn patients admitted to a hospital without a burn center or referred to a burn center. Methods This retrospective, nationwide, cohort study included patients with burns or inhalation trauma, admitted between 2014 and 2018, from a national trauma registry. The primary outcome measure was admission to a hospital with or without a burn center. Secondary outcome measures were patient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
1
2
1
Order By: Relevance
“…Burns were more frequent among men (61.6%)-a global trend due to the predominance of men working in metallurgy or agriculture. In our review, this incidence was somewhat lower than that reported in 1998 (64%), 2008 (65%), and 2018 (66%) 21,25,26 , and is consistent with the trend observed in other developed countries [6][7][8]15,[27][28][29][30] . In Palacios 31 , however, 51% of burn patients were men.…”
Section: Demographicssupporting
confidence: 91%
See 2 more Smart Citations
“…Burns were more frequent among men (61.6%)-a global trend due to the predominance of men working in metallurgy or agriculture. In our review, this incidence was somewhat lower than that reported in 1998 (64%), 2008 (65%), and 2018 (66%) 21,25,26 , and is consistent with the trend observed in other developed countries [6][7][8]15,[27][28][29][30] . In Palacios 31 , however, 51% of burn patients were men.…”
Section: Demographicssupporting
confidence: 91%
“…Mortality remained at 3.5% (0% in children under 16 years of age and 4.3% in adults). This rate is somewhat higher than that reported in most developed European countries 6 , 10 , 15 , 65 , 66 .…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…At present, about 265,000 people worldwide have died of burns (14). It has been reported that the incidence of burns was 0.19% in the United States, 2.43% in Southeast Asia, and 1.87% in the Mediterranean (15)(16)(17)(18). In China, >20 million patients suffer from different degrees of burns (19).…”
Section: Discussionmentioning
confidence: 99%